Progress towards Bioorthogonal Catalysis with Organometallic Compounds1. Issue 39 (19th August 2014) - Völker, Timo; Dempwolff, Felix; Graumann, Peter L.; Meggers, Eric
Abstract The catalysis of bioorthogonal transformations inside living organisms is a formidable challenge—yet bears great potential for future applications in chemical biology and medicinal chemistry. We herein disclose highly active organometallic ruthenium complexes for bioorthogonal catalysis under biologically relevant conditions and inside living cells. The catalysts uncage allyl carbamate protected amines with unprecedented high turnover numbers of up to 270 cycles in the presence of water, air, and millimolar concentrations of thiols. By live‐cell imaging of HeLa cells and with the aid of a caged fluorescent probe we could reveal a rapid development of intense fluorescence within the cellular cytoplasm and therefore support the proposed bioorthogonality of the catalysts. In addition, to illustrate the manifold applications of bioorthogonal catalysis, we developed a method for catalytic in‐cell activation of a caged anticancer drug, which efficiently induced apoptosis in HeLa cells.